The phenomenon of fan creativity: the main directions of studies - Leila O. Algavi; Alina V. Kharchenko (RUDN Journal of Studies in Literature and Journalism, 2020)
The article considers the main directions of foreign and domestic studies of fan communities and fan creative production. The article synthesizes theoretical knowledge collected abroad. Media fandoms are understood as interpretive, participatory communities that are able to influence media production. Fanfiction is shown as one of the forms of expression of criticism and various potential interpretations and meanings of the original work. The Russian scientific community also refers to fan communities as interpretive communities. Fanfiction is defined as a literary work that performs the function of demonstrating a variety of individual readers interpretations of the work. It was revealed that despite the existence of some differences in approaches to the study of fan creativity, there is a common focus on the activity of the audience. More attention is given to the study of collective meaning-making and ways of expressing different interpretations of the original media product.